Expecting the unexpected: preventing and managing the consequences of coronary perforations. (2nd November 2018) - Tajti, Peter; Xenogiannis, Iosif; Chavez, Ivan; Gössl, Mario; Mooney, Michael; Poulose, Anil; Sorajja, Paul; Traverse, Jay; Wang, Yale; Burke, M. Nicholas; Brilakis, Emmanouil S.
ABSTRACT: Introduction : Coronary artery perforations are more likely to occur during percutaneous coronary intervention of complex coronary lesions, such as heavily calcified lesions and chronic total occlusions. Areas covered : Authors provide an update on the management of coronary perforations by performing a critical review of the related, recently published literature. Expert commentary : Meticulous attention to guidewire position and to device selection is critical for minimizing the risk for coronary perforation. If a perforation occurs, following a structured, algorithmic approach can maximize the likelihood of a successful outcome.